Leishmania Antigenuria to Predict Initial Treatment Failure and Relapse in Visceral Leishmaniasis/HIV Coinfected Patients: An Exploratory Study Nested Within a Clinical Trial in Ethiopia - van Griensven, Johan; Mengesha, Bewketu; Mekonnen, Tigist; Fikre, Helina; Takele, Yegnasew; Adem, Emebet; Mohammed, Rezika; Ritmeijer, Koert; Vogt, Florian; Adriaensen, Wim; Diro, Ermias (Frontiers in Cellular and Infection Microbiology, 2018)
Background: Biomarkers predicting the risk of VL treatment failure and relapse in VL/HIV coinfected patients are needed. Nested within a two-site clinical trial in Ethiopia (2011–2015), we conducted an exploratory study to assess whether (1) levels of Leishmania antigenuria measured at VL diagnosis were associated with initial treatment failure and (2) levels of Leishmania antigenuria at the end of treatment (parasitologically-confirmed cure) were associated with subsequent relapse. Methods:Leishmania antigenuria at VL diagnosis and cure was determined using KAtex urine antigen test and graded as negative (0), weak/moderate (grade 1+/2+) or strongly-positive (3+). Logistic regression and Kaplan-Meier methods were used to assess the association between antigenuria and (1) initial treatment failure, and (2) relapse over the 12 months after cure, respectively. Results: The analysis to predict initial treatment failure included sixty-three coinfected adults [median age: 30 years interquartile range (IQR) 27–35], median CD4 count: 56 cells/μL (IQR 38–113). KAtex results at VL diagnosis were negative in 11 (17%), weak/moderate in 17 (27%) and strongly-positive in 35 (36%). Twenty (32%) patients had parasitologically-confirmed treatment failure, with a risk of failure of 9% (1/11) with KAtex-negative results, 0% (0/17) for KAtex 1+/2+ and 54% (19/35) for KAtex 3+ results. Compared to KAtex-negative patients, KAtex 3+ patients were at increased risk of treatment failure [odds ratio 11.9 (95% CI 1.4–103.0); P: 0.025]. Forty-four patients were included in the analysis to predict relapse [median age: 31 years (IQR 28–35), median CD4 count: 116 cells/μL (IQR 95–181)]. When achieving VL cure, KAtex results were negative in 19 (43%), weak/moderate (1+/2+) in 10 (23%), and strongly positive (3+) in 15 patients (34%). Over the subsequent 12 months, eight out of 44 patients (18%) relapsed. The predicted 1-year relapse risk was 6% for KAtex-negative results, 14% for KAtex 1+/2+ and 42% for KAtex 3+ results [hazard ratio of 2.2 (95% CI 0.1–34.9) for KAtex 1+/2+ and 9.8 (95% CI 1.8–82.1) for KAtex 3+, compared to KAtex negative patients; P: 0.03]. Conclusion: A simple field-deployable Leishmania urine antigen test can be used for risk stratification of initial treatment failure and VL relapse in HIV-patients. A dipstick-format would facilitate field implementation.